INTERNET SAFETY EDUCATION: HOW WE EDUCATE OUR GIRLS TO BEWARE OF OTHERS, AND OUR BOYS TO BEWARE OF THEMSELVES - Steinfeld, Nili (AoIR Selected Papers of Internet Research, 2019)
Alongside its many advantages, the Internet presents a variety of challenges and risks to adolescents. From a perspective focusing on information flow processes, this study distinguishes between risks resulting from _exposure to information_, i.e. exposure of adolescents to inappropriate content: Harmful, sexual or violent, and risks resulting from _exposure of information_, i.e. disclosure of personal information online, privacy harms inflicted by the user or others, misuse of personal information which can result in identity theft, physical and sexual assault. The study examines gender differences in perceptions regarding adolescents’ online uses, habits and risks, and whether these lead to differences in emphasis of educational messages delivered by parents and teachers to adolescents. Based on a mixed-method study combining survey conducted among 513 adolescents and 50 semi-structured interviews with educators and adolescents, the findings illustrate how a common perception that girls share more personal information online and are (consequently) more vulnerable to online predators leads to more emphasis given on implications of personal information disclosure in messages delivered to girls. On the other hand, boys are considered naughty and nosy, searching for “forbidden”, mainly sexual, content, and emphasis is given on limiting and monitoring their searches and video consumption. Apparently, although parents, teachers and adolescents proclaim to be aware of the similar risks to boys and girls online, there is a message interwoven in internet safety education discourse: Girls are to be aware of others looking to harm them, and boys are to be aware of themselves, their curiosity and evil inclination.